PEMBERDAYAAN "TEACHER-PARENT PARTNERSHIP" UNTUK MENINGKATKAN PARTISIPASI PESERTA DIDIK KELAS XI IPA 1 SMA NEGERI 7 YOGYAKARTA - Herawati, Reni (Caraka Olah Pikir Edukatif, 2015)
This paper presents the writer's experience in implementing a learning approach to build students' motivation by empowering parental partnership. Teaching English, especially, at class XI IPA 1, SMA N 7 Yogyakarta, is very challenging. However, the writer as the teacher found some problems in learning process. It was her task to create an effective learning process, therefore, she had to manage the class into active and motivated classes. The class consisted of 24 students who were commonly silent and passive. Their class participation especially in speaking class was far from the expected. This had led the writer to make an effort to fid a learning approach to be implemented in her speaking class. The writer performed an approach by Empowering "Teacher-Parent Partnership" to Enhance Class Participation among Students of XI IPA 1 at SMA Negeri 7 Yogyakarta. This paper was aiming at describing the effectiveness of "Teacher-Parent Partnership" as an approach to enhance students' participation and explaining how it could enhance speaking capability among the students of SMA N 7 Yogyakarta. The writer was really sure that parents' involvement in children's education is highly correlated with children success at school. She took a deep concern since she found that the teacher-parent partnership, so far, was only done but to make communication about school fee, regulation, and school programs. Meanwhile, only few teachers realize that personal communication between teacher and parents, especially about the progress of the children at class, was very important. The writer was really sure that parents' involvement was needed; she decided to empower parental partnership to build the students' motivation. The implementation of empowering teacher-parent partnership used several ways of communication: 1) email and letter, 2) news-letter, 3) telephone, 4) meeting. Some valuable fidings were proven. The communication between teacher and parent led a new atmosphere in the class. Among students, teachers and parents could be closer. It gave an amazing power to build students' motivation. They were creating conducive class. They were getting better gradually in English learning. In a nut shell, "Empowering Teacher-Parent Partnership" was proven to be an effective approach to solve the problems of lack participation at Class XI IPA 1, SMAN 7 Yogyakarta and to enhance the students' competence of speaking. Key words: teacher-parent partnership, learning approach, students' participation, Key words:English learning